Self-assembly of peptide nanocapsules by a solvent concentration gradient - Li, Haopeng (2024)
Biological systems can create materials with intricate structures and specialized functions. In comparison, precise control of structures in human-made materials has been challenging. Here we report on insect cuticle peptides that spontaneously form nanocapsules through a single-step solvent exchange process, where the concentration gradient resulting from the mixing of water and acetone drives the localization and self-assembly of the peptides into hollow nanocapsules. The underlying driving force is found to be the intrinsic affinity of the peptides for a particular solvent concentration, while the diffusion of water and acetone creates a gradient interface that triggers peptide localization and self-assembly. This gradient-mediated self-assembly offers a transformative pathway towards simple generation of drug delivery systems based on peptide nanocapsules.